NEOROMANTICISM IN THE HISTORICAL LEGACY OF V. LYPYNSKYI: CONTEMPORARY INTERPRETATIONS (Південний архів (історичні науки), 2025)
The purpose of this article is to establish the main approaches of Lypynskyi scholars in defining the role of neoromanticism as an ideological framework in the historical thought of V. Lypynskyi. Research Methods. The study employs methods of historiographical analysis and synthesis, which have been used to determine the key contributions of Lypynskyi scholars in this field. Research Results. The article analyzes contemporary studies that explore the neoromantic elements in Lypynskyi’s works. Conclusions. Scholars such as O. Yas and V. Masnenko do not consider V. Lypynskyi a historian of the classical academic type. This view is justified by his use of neoromantic methods, which extend beyond the boundaries of traditional positivist analysis. Through these methods, Lypynskyi glorified prominent Ukrainian historical figures, integrated principles of vitalism and stylistic features of neoromantic semantics, combined various irrational methods with rational positivist principles, skillfully employed symbolism, and incorporated both voluntarism and determinism into his theoretical constructs. Influenced by neoromantic principles, he developed his own cyclical concept of history, blending irrational approaches with sociological analysis. In his later works, Lypynskyi integrated the idea of organicism into his historiosophy – an inherently neoromantic and irrational concept – according to which the nation was perceived as a holistic organism governed by natural and social cycles.
Keywords: Viacheslav Lypynskyi, contemporary historiography of Lypynskyi studies, neoromantic methodology, scientific principles of neoromanticism, neoromantic analytical tools